Relationship between emotional intelligence and job satisfaction among employees at Social Security Organization (SOCSO) Jalan Ampang / Rabiatun Adawiyah Ahmad Zaini - Ahmad Zaini, Rabiatun Adawiyah (Faculty of Business and Management, 2018)
This study has intended to examine the relationship between emotional intelligence and job satisfaction among employees in Social Security Organization (SOCSO) at Jalan Ampang. This relationship was examined based on variables in emotional intelligence which is Other emotion appraisal, Use of emotion, Self-emotion appraisal and Regulation of emotion. This study use quantitative method whereby set of questionnaires are used to collect the data. There were 113 of data respondents. The data analyses in this study were analysed by using the IBM SPSS statistics software. Descriptive statistics were used to measure relationship between emotional intelligence and job satisfaction. Meanwhile, testing of means analysis, Pearson Coefficient and regression analysis were performed to examine the relationship between emotional intelligence and job satisfaction. Results indicate the there is a strong significant relationship between emotional intelligence and job satisfaction. The discussions of study implications and future research will be explained at the end of this study.